2020
DOI: 10.2139/ssrn.3615077
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the Future of Microfinance: Evidence and Insights from Pakistan

Abstract: The COVID-19 pandemic threatens lives and livelihoods, and, with that, has created immediate challenges for institutions that serve affected communities. We focus on implications for local microfinance institutions in Pakistan, a country with a mature microfinance sector, serving a large number of households. The institutions serve populations poorly-served by traditional commercial banks, helping customers invest in microenterprises, save, and maintain liquidity. We report results from 'rapid response' phone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Various studies have pointed out the severe, direct economic impacts of lockdowns of public life on the global poor ( Aushian and Abuya, 2020 , BRAC, 2020 , HSRC, 2020 , Kesar et al, 2020 , Le Nestour et al, 2020 , Malik et al, 2020 , Rahman and Matin, 2020 , Sumner et al, 2020 ). However, few studies in low-income settings analyze the impact of lockdowns on other dimensions of well-being, such as schooling of children, health concerns, and emotional stress, which can, in turn, be triggered by direct income loss, anxieties about future income, reduced social interaction, and isolation at home.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have pointed out the severe, direct economic impacts of lockdowns of public life on the global poor ( Aushian and Abuya, 2020 , BRAC, 2020 , HSRC, 2020 , Kesar et al, 2020 , Le Nestour et al, 2020 , Malik et al, 2020 , Rahman and Matin, 2020 , Sumner et al, 2020 ). However, few studies in low-income settings analyze the impact of lockdowns on other dimensions of well-being, such as schooling of children, health concerns, and emotional stress, which can, in turn, be triggered by direct income loss, anxieties about future income, reduced social interaction, and isolation at home.…”
Section: Resultsmentioning
confidence: 99%
“…Various previous studies already show that, as of today, the pandemic has had a larger economic than health impact on people living in poverty ( Aushian and Abuya, 2020 , BRAC, 2020 , HSRC, 2020 , Kesar et al, 2020 , Le Nestour et al, 2020 , Malik et al, 2020 , Rahman and Matin, 2020 , Sumner et al, 2020 ). This outcome also seems to be the case for the urban poor in Accra, where many people are dependent on their own business in the informal economy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As a result, in Pakistan the government also announced complete lockdown from March 23 to May 9, 2020, involving various sectors including educational institutes, businesses and public transport in all the provinces. As per the government guidelines, people employed in formal sector enjoyed job security and were also being paid during this lockdown, but those associated with informal sector had no access to all these benefits, and most of them were suspended (Malik et al 2020). From the global instances, it was analysed that the daily wagers, street vendors, domestic helpers, people involved in courier and delivery services, cleaners and waste collection personnel possess the maximum disease exposure risk.…”
Section: Employment Layoffsmentioning
confidence: 99%
“…But the details of how these costs have played themselves out have varied enormously from country to country. Evidence from Pakistan, for instance, suggests that microfinance in low-income communities now faces a drastic crisis ( Malik et al , 2020 , this issue). Rapid-response surveys suggest that on average, week-on-week sales among microenterprise owners and household income both fell by about 90 per cent, households’ primary immediate concern in early April became how to secure food, and about 70 per cent of the sample of current microfinance borrowers reported that they could not repay their loans.…”
Section: The Medical Crisis and Its Economic Effectsmentioning
confidence: 99%